(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This study has pursued to identify the agricultural initiative (the independent variable) with all its subordinate variables in profits and bank lending activity (the dependent variable), as an applied study in cooperative agricultural bank, which stemms from a problem that includes:- • The policy variance of agricultural initiative lending and variation of the cooperative agricultural bank lending policies. • decreasing the demand on the loans of the cooperative agricultural bank and increasing the demand on the agricultural initiative by the individuals (citizens). The purpose of the study is represented by clarifying the practical reality of applying the agricultural initiative and its reflections on the revenues and loans of the cooperative agricultural bank, as well as, explaining the theoretical frames and intellective denotations of the study’s variables . Specific recommendations have been set as follows: • There is a need for establishing a joint coordination committee that takes into account specifying the validity, duties and tasks of all participating parts in implementing and supporting the agricultural initiative. • Re-estimating and assessing the lending policies of the agricultural initiative, in accordance with the cooperative agricultural bank lending policy.